A gift of prophecy : the phenomenal Jeane Dixon - Montgomery, Ruth Shick, 1912-2001. (New York, Morrow, 1965)
A Gift of Prophecy tells the story of the extraordinary Jeane Dixon who predicted: the assassination of President John F. Kennedy and the name of his killer; Teddy Kennedy's accident; the assassination of Mahatma Gandhi; Dag Hammarskjold and Carole Lombard's deaths by plane; Marilyn Monroe's suicide; and numerous other events of personal, national and international significance. In the past quarter century, Jeane Dixion has become as much an institution in Washington as the Pentagon. Her amazing ability to see into the future has her constantly beseiged by people anxious to know what the future holds for them. Yet Mrs. Dixon remains an extremely religious woman who uses her gift only for the good of humanity, and continually refuses monetary compensation.
Keywords: Dixon, Jeane